Management level of using digital services Bank Syariah Indonesia (BSI) KCP ipuh - Yulita, Yesi; Apriza, Mutiara; Wulandari, Silvi; Isnaini, Desi; Arisandy, Yosy (BIMA Journal (Business, Management, & Accounting Journal), 2021)
PT Bank Syariah Indonesia (BSI)  Ipuh Branch Office having its address at Pulai Payung Village, Ipuh sub-district, Muko-muko district, Bengkulu province. In carrying out its activities, the Bank Syariah Indonesia (BSI)  Ipuh branch continues to innovate products and develop excellent service to customers to improve the company's professionalism. The purpose of this study is to find out the projected level of use of the idigital bank Syariah Indonesia (BSI)  iKcp iIPuh  service. The research method used is a qualitative field research with a descriptive research approach. Methods of collecting data by means of observation, interviews and documentation. Informants in this study were employees of Bank Syariah Indonesia (BSI)  Kcp Ipuh and Bank Syariah Indonesia (BSI) customers of Bank Syariah Indonesia (BSI)  Kcp Ipuh. The results of  this study can be concluded that the level of use of digital services at Bank Syariah Indonesia (BSI)  Kcp Ipuh has increased. This is because Bank Syariah Indonesia (BSI) services during the COVID-19 pandemic are demanded to be faster, easier, and more flexible. The rapid growth of the Internet is changing the way companies connect with their consumer icons, the Bank Syariah Indonesia (BSI) business is no exception. Using the idigital Bank Syariah Indonesia (BSI)  iKcp IPuh i has many advantages. i the ease of research results from the IBank Syariah Indonesia (BSI)  iKcp iIpuh i consumeni to give an opinion or respond that i: i(1) lack of understanding among the public about how to use the idigital banking application, i(2) i Ease of transacting using digital Bank Syariah Indonesia (BSI) without having to go to a bank, (3) ease of customers in using the application and fast in solving problelems in using  idigital iBank Syariah Indonesia (BSI). in determining the digital Bank Syariah Indonesia (BSI), namely: Can perform transactions, administrative procedures and implementation of itransfer to all customers so that they can know that the customer has no doubts in conducting IBank Syariah Indonesia (BSI)  transactions through idigital.